Pengaruh Rhythm Therapy Terhadap Perkembangan Motorik, Sensori Dan Gejala Pada Anak Autism Spectrum Disorder Children (ASD) - Erna Ariyanti Kurnianingsih; Erayanti Saloko (Poltekkes Kemenkes Surakarta, 2019)
Background: Music is long known to have therapeutic effect. It can be a mean to improve adaptive behavior, communication, functioning, and understanding of emotion for ASD Children. In form of rhythm therapy, music is mainly used to stimulate rhythm internalization to achieve better focus and more coordinated movements. In addition to its use to obtain non-musical skills, rhythm therapy can also achieve client occupational performance in playing musical instruments. Method: The design of this study is quasi experiment with control group pretest-posttest design. 30 samples of ASD ages 3 -10 years were divided into groups of intervention using rhythm therapy, and control group using occupational therapy standard for 12 weeks .The Test of Gross Motor Development (TGMD), Short Sensory Profile (SSP)and Gilliam Autism Rating Scale (GARS) were administered before and after intervention. Result: The Mann U Whitney result showed TGMD scores showed 0.125 ( p > 0,05), SSP scores showed 0,000 (p< 0,05) and GARS scores showed 0,001 ( p< 0,05). Conclusion: It can be concluded that there was no effect of rhythm therapy on motor of ASD children. There is an effect of rhythm therapy ob sensory of ASD Children, and there is an effect of rhythm therapy on the symptoms of ASD Children